«The anime business»: the history of anime and general review of anime’s market - Aхaпов, Е. A.; Бaубекқызы, Ж. (Journal of Oriental Studies, 2017)
In recent years, overseas Japanese animation was called “anime”. Anime has crossed the border, where it is called “comics for children” now has a high popularity among both adults and children. Define the anime “cartoon simple” - makes it impossible to show the variety of deep of anime. In the anime products have all the elements, like a novel, drama, tragedy, comedy, history, residents of foreign countries that used to watch movies. Anime affects some psychological topics that are not shown in the Euro-American movies “- says Susan J. Napier.. But for most people in Kazakhstan anime it is still children’s cartoon “exclusively for children.” In this regard, the article being acquainted, describes the anime as the one part of Japanese culture, anime stories and being a general overview on the anime market.